The Notch Ligand Jagged1 as a Target for Anti-Tumor Therapy - Li, Demin; Masiero, Massimo; Banham, Alison H.; Harris, Adrian L. (Frontiers in Oncology, 2014)
The Notch pathway is increasingly attracting attention as a source of therapeutic targets for cancer. Ligand-induced Notch signalling has been implicated in various aspects of cancer biology; as a consequence pan-Notch inhibitors and therapeutic antibodies targeting one or more of the Notch receptors have been investigated for cancer therapy. Alternatively, Notch ligands provide attractive options for therapy in cancer treatment due to their more restricted expression and better-defined functions, as well as their low rate of mutations in cancer. One of the Notch ligands, Jagged1 (JAG1), is overexpressed in many cancer types, and plays an important role in several aspects of tumour biology. In fact, JAG1-stimulated Notch activation is directly implicated in tumour growth through maintaining cancer stem cell populations, promoting cell survival, inhibiting apoptosis and driving cell proliferation and metastasis. In addition, JAG1 can indirectly affect cancer by influencing tumour microenvironment components such as tumour vasculature and immune cell infiltration. This article gives an overview of JAG1 and its role in tumour biology, and its potential as a therapeutic target.